G protein-coupled receptors for energy metabolites as new therapeutic targets - Blad, Clara C.; Tang, Cong; Offermanns, Stefan (Nature reviews. Drug discovery, 2012)
Several G protein-coupled receptors (GPCRs) that are activated by intermediates of energy metabolism — such as fatty acids, saccharides, lactate and ketone bodies — have recently been discovered. These receptors are able to sense metabolic activity or levels of energy substrates and use this information to control the secretion of metabolic hormones or to regulate the metabolic activity of particular cells. Moreover, most of these receptors appear to be involved in the pathophysiology of metabolic diseases such as diabetes, dyslipidaemia and obesity. This Review summarizes the functions of these metabolite-sensing GPCRs in physiology and disease, and discusses the emerging pharmacological agents that are being developed to target these GPCRs for the treatment of metabolic disorders.
Gesehen am 07.11.2018